Dealing with food safety concerns among urban poor when eating out: social practices in Dhaka, Bangladesh - Haque, Md. Latiful; Oosterveer, Peter; Vignola, Raffaele; Rasheed, Sabrina (Frontiers in Sustainable Food Systems, 2023)
The article explores eating-out practices among poor urban consumers in the Bangladesh and their strategies to cope with food safety concerns. Using social practice theory, we implemented interviews and a household survey to analyse the eating-out practices of adult slum dwellers in Dhaka, Bangladesh and their food safety coping strategies. We identified two different dominant eating out practices: 'snacking' and 'having a complete meal'. By reviewing the food safety concerns and coping strategies, we found that despite varying concerns, coping strategies are broadly similar across these two practices. The concerns include food presentation, unhygienic conditions, and unknown processing, while searching for information, using heuristic tools, and avoidance are the main coping strategies. These strategies are applied in both practices and do not exhibit significant differences in socioeconomic considerations and safety concerns. This indicates that the urban poor lack the resource and competencies to manage their concerns. The conclusion section presents a conceptual framework for future research on food safety coping strategies in urban eating-out practices. We also underline the need for context-specific policy interventions to ensure food safety in the urban food system of the global south.